2012
DOI: 10.1152/jn.01073.2011
|View full text |Cite
|
Sign up to set email alerts
|

Temporal precision and reliability in the velocity regime of a hair-cell sensory system: the mechanosensory lateral line of goldfish,Carassius auratus

Abstract: Fish and aquatic frogs detect minute water motion by means of a specialized mechanosensory system, the lateral line. Ubiquitous in fish, the lateral-line system is characterized by hair-cell based sensory structures across the fish's surface called neuromasts. These neuromasts occur free-standing on the skin as superficial neuromasts (SN) or are recessed into canals as canal neuromasts. SNs respond to rapid changes of water velocity in a small layer of fluid around the fish, including the so-called boundary la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 69 publications
1
13
0
Order By: Relevance
“…However, physically blocking the canal organs of the blind cave fish Anoptichthys jordani indicated that superficial neuromasts detected prey items that produce vibratory stimuli (Abdel-Latif et al, 1990). The vibrations emitted by Artemia are ≤10Hz (Barlow and Sleigh, 1980), at the low end of the detection range of superficial neuromasts, at least in goldfish, Carassius auratus (Goulet et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, physically blocking the canal organs of the blind cave fish Anoptichthys jordani indicated that superficial neuromasts detected prey items that produce vibratory stimuli (Abdel-Latif et al, 1990). The vibrations emitted by Artemia are ≤10Hz (Barlow and Sleigh, 1980), at the low end of the detection range of superficial neuromasts, at least in goldfish, Carassius auratus (Goulet et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Here we focus on temporal codes, in which the precise timing of action potentials carries information (Lestienne, 2001;Theunissen and Miller, 1995). Temporal codes have been implicated in the processing of somatosensory (Jones et al, 2004), olfactory (Laurent, 1997), gustatory (Di Lorenzo et al, 2009), visual (Victor and Purpura, 1996), auditory (deCharms and Merzenich, 1996), vestibular (Sadeghi et al, 2007), mechanosensory lateral line (Goulet et al, 2012) and electrosensory stimuli (Carlson, 2008b).…”
Section: Introductionmentioning
confidence: 99%
“…The force acting on the cupula and thus the shear stress that is acting on the neuromast [Prandtl 1904; Schlichting and Gersten 1979] depends on the water velocity as higher water velocities result in a thinner boundary layer. This renders the movement of the cupula, and hence the responsiveness of the superficial neuromasts, sensitive to the velocity of local water motion [Chagnaud et al 2008a; Chagnaud et al 2008b; Engelmann et al 2002; Goulet et al 2008; Goulet et al 2012; Kroese and Schellart 1992; Kroese et al 1978; Voigt et al 2000]. The sensitivity of canal neuromasts depends on both, the filter properties of the cupula (see above) and the morphology of the canal.…”
Section: Hair Cell Mechanoreceptive Organs - Peripheral Organization mentioning
confidence: 99%
“…For the superficial neuromast system the precision of this encoding strategy is remarkable (Fig. 5C) [Goulet et al 2012], suggesting that the low sensitivity pathway is well suited to encode the minute spatio-temporal differences characteristic for global flow fields, i.e., hydrodynamic patterns spanning an animals sensory surface (Fig. 5B).…”
Section: Hair Cell Mechanoreceptive Organs - Peripheral Organization mentioning
confidence: 99%